Enhancing the biomethane yield of groundnut shells using deep eutectic solvents for sustainable energy production - Olatunji, Kehinde O.; Madyira, Daniel M. (Frontiers in Energy Research, 2024)
This study examined the influence of DES pretreatment using choline chloride and ethyl glycerol with the molar ratio of 1: 1 at different solid:liquid ratios and temperatures on groundnut shells’ microstructural arrangement and biomethane yield. Scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR) were used to study the effects of pretreatment on microstructural arrangements, and the pretreated substrate was digested at mesophilic temperature to determine its biomethane potential. The result of SEM analysis indicated that DES pretreatment alters the microstructural arrangement of groundnut shells, and XRD analysis showed an optimum crystallinity index of 20.71% when the substrate with a solid:liquid ratio of 1:2 was experimented at 80°C. The highest theoretical biomethane yield of 486.81 mL CH4/gVSadded was recorded when the substrate with a 1:4 solid:liquid ratio was investigated at 100°C, and the highest biodegradability rate (84.87%) was observed from the substrate treated with a 1:2 solid:liquid ratio at 100°C. The optimum biomethane yield of 365.70 mL CH4/gVSadded, representing a 226.05% increase, was observed from 1:2 of solid:liquid ratios at 100°C. Therefore, DES pretreatment using choline chloride and ethyl glycerol is a bright, low-cost pretreatment method for enhancing the biomethane yield of lignocellulose feedstocks.